Identification of organic fouling agents on activated carbon by evolved gas analysis. - Fisher, Nicholas G. (Curtin University, 2000)
Activated carbon is widely used in the gold processing industry as an adsorbent for the gold cyanide complex, [Au(CN)(subscript)2]. However, many other processing reagents are also adsorbed (termed fouling), which compete with the gold cyanide complex for active sites on the carbon. So far the only way of assessing the amount of fouling due to organic compounds that has adsorbed on the carbon is through the use of thermogravimetry (TG). Unfortunately, thermogravimetry only gives the percentage total of organic fouling agents adsorbed and no information can be obtained on the identity of the individual organic fouling agents. Thus this current work reports the development of analytical methods capable of identifying specific fouling agents.In this thesis the identification of two types of common organic fouling agents adsorbed on activated carbon during gold processing has been established using three thermal analysis techniques, namely thermal desorption-pyrolysis-gas chromatography-mass spectrometry (TD-py-GC-MS), thermogravimetry-mass spectrometry (TG-MS), and thermogravimetry-Fourier transform infrared (TG-FTIR) spectroscopy. TD-py-GC-MS was used to identify the individual decomposition gases of each sample. TG-MS and TG-FTIR were used to obtain the decomposition temperatures of the fouling agents, and to identify/monitor the gases evolved as a function of temperature. All analyses were performed in an inert atmosphere.The organic fouling agents studied were xanthates and frothing agents, which are used as flotation reagents. The xanthates studied were sodium ethyl xanthate (SEX), sodium isobutyl xanthate (SiBX), potassium ethyl xanthate (PEX), and potassium amyl xanthate (PAX). The frothing agents studied were polypropylene glycol (PPG), polypropylene glycol methyl ether (PPGME), alpha-terpineol, and methyl isobutyl carbinol (MiBC). The thermal decomposition of each pure reagent was studied, and then the reagents were individually adsorbed on an activated carbon (Haycarb, -45 mu m) and their thermal decomposition reinvestigated. These pure systems were then compared to the thermal decomposition of activated carbon samples taken from two gold processing plants.Between seven and sixteen gases were identified via TD-py-GC-MS for the decomposition of each xanthate. Common gases and types of gases identified included carbonyl sulfide, carbon disulfide, thiols, alcohols, carbonates, sulfides, disulfides, and carbonothioic acid, O,S, dialkyl esters. The thermogravimetric curve of each xanthate displayed two mass losses. The mass losses and their corresponding temperatures were dependent on the alkyl chain and alkali cation of the xanthate. TG-MS and TG-FTIR showed carbonyl sulfide and carbon disulfide were the most significant gases evolved from the decomposition of each xanthate.Each xanthate was adsorbed on activated carbon, and its thermal decomposition characteristics reinvestigated. On heating, similar gases were evolved to those detected for the xanthate alone. However, the TG curves displayed three mass losses compared to two with the xanthates not adsorbed on activated carbon. The first mass loss of each sample was attributed to a hydrolysis reaction between water retained in the activated carbon and the xanthate. TG-MS and TG-FTIR analyses showed carbon disulfide and carbonyl sulfide were the most significant gases evolved during the first mass loss and second mass losses respectively, and consequently these gases could be used as indicators of xanthate fouling on plant samples.The TD-Py-GC-MS, TG-MS, and TG-FTIR analyses of the frothing agents showed these compounds mainly boiled with little indication of thermal decomposition. The thermogravimetric curve of each frother displayed one mass loss. Upon reinvestigation of the frothing agents individually adsorbed on activated carbon, a number of different gases were identified by the TD-py-GC-MS analyses. For all adsorbed frothing agents (except MiBC) these included propanal, 2-ethyl-4-methyl1,3-dioxolane, 3,3-oxybis-2-butanol, and dioxanes. Each TG curve displayed one mass loss due to the decomposition of the frothing agent. The TG-MS and TG-FTIR analyses showed propanal was the most significant gas evolved for the PPG and PPGME. For alpha-terpineol, propene was also a significant gas, although this gas was not detected by TG-FTIR. The TD-py-GC-MS and TG-FTIR analyses of the MiBC showed it mainly boiled off the carbon without significant alteration.Four activated carbon samples were obtained from different parts of the process circuit in the Three Mile Hill plant in Western Australia. Nine to twelve gases were identified by TD-py-GC-MS analysis of each sample. Common gases included butene, 2-methyl-I-butene, and butanol. The TG curve of each sample displayed one mass loss due to the presence of fouling agents. TG-MS analyses showed butene was the most significant gas evolved for this mass loss. TG-FTIR analyses showed that carbonyl sulfide had also evolved during this mass loss. Thus it was concluded from the detection of carbonyl sulfide and its temperature of evolution, that fouling of the activated carbon by a xanthate had occurred.Five activated carbon samples were obtained from the Salsigne plant in France. Nine to fourteen gases were identified by TD-py-GC-MS analysis of each sample. Common gases included cyclopropane, butene, propanal, isobutanol, isoarnyl alcohol, and 2,5 and 2,6-dimethyl dioxene. The TG curve of each sample displayed one mass loss due to the decomposition of fouling agents, in the same temperature region as the Three Mile Hill samples. TG-MS analyses showed cyclopropane was the most significant gas evolved for this mass loss. TG-FTIR analyses showed that carbonyl sulfide had also evolved during this mass loss. Thus it was concluded from the detection of propanal, carbonyl sulfide, and their temperatures of evolution that fouling of the activated carbon by a xanthate and a frothing agent had occurred respectively.A comparison of the techniques showed that TD-py-GC-MS analysis was essential for unambiguous identification of the complex gas mixture obtained from decomposition of organic fouling agents. Unfortunately TD-py-GC-MS provided no information on mass losses or temperatures of gas evolution. TG-MS permitted the monitoring of evolved gases versus temperature via their molecular ions. However the molecular ion signals were affected by overlapping fragment and/or isotope ion signals. The TG-FTIR was most useful when the evolved gases gave an infrared adsorption that was very characteristic of the molecule, as for the identification of carbonyl sulfide and carbon disulfide. This work was successful as a combination of the analytical techniques enabled identification of fouling agents adsorbed on plant samples.